2015
DOI: 10.1080/10548408.2015.1068264
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tour Guides’ Physical Attractiveness, Sense of Humor, and Seniority on Guide Attention and Efficiency

Abstract: In this study, we investigated whether tourists view attractive tour guides as more competent, humorous tour guides as more approachable, and experienced tour guides as more professional, and whether these three factors influence the effectiveness of tour guide interpretation. The results indicated that physical attractiveness and humor had additive effects on interpretation effectiveness when combined. Although some tour guides were not physically attractive, experience provided an additive effect on interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…A. Lee and Oh 2017; Pearce and Pabel 2015). Third, tour guides who interpret destinations in a humorous way could capture tourists’ attention (Kuo et al 2016; Tsai, Wang, and Tseng 2016). Then, tourists, who find it easier to perceive an attractive destination image, such as a unique historical culture, scenery in style, and unknown allusions, will be more like to engage in favorable behavior toward the destination (H.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A. Lee and Oh 2017; Pearce and Pabel 2015). Third, tour guides who interpret destinations in a humorous way could capture tourists’ attention (Kuo et al 2016; Tsai, Wang, and Tseng 2016). Then, tourists, who find it easier to perceive an attractive destination image, such as a unique historical culture, scenery in style, and unknown allusions, will be more like to engage in favorable behavior toward the destination (H.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…With the help of humorous expressions and behaviors, guides in group tourism can help them have an enjoyable experience (Pabel and Pearce 2016, 2018; Tsaur and Teng 2017). This is because tour guide humor can attract individual attention and provide many unknown and interesting stimuli for tourists (Tsai, Wang, and Tseng 2016; Tsaur and Teng 2017). Therefore, tour guide humor has a stronger impact on positive emotion of tourists with low openness than those with high openness.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have indicated that these traits include cheerfulness (J. Y. Wong and Wang 2009), a sense of humor (Heung 2008; Pabel and Pearce 2016; Tsai, Wang, and Tseng 2016), extroversion (Mancini 2001), and high emotional intelligence (Min 2012; Tsaur and Ku 2019). However, these studies tend toward one-dimensional thinking, exploring a single feature (ie, sense of humor) and overlooking the multidimensional roles involved in TC work.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, articles exploring other aspects of guiding are gradually appearing. These deal with various topics: the stresses and emotions present in the relationship between the guide and the tour operator (e.g., McKerzie & Kerr, ); locals doing guided tours in the own city (e.g., Diaz‐Soria, ); the phenomenon of zero fare in guiding (e.g., Xu & McGehee, ); hassles in the personal life and work of tour guides (e.g., Tsaur & Lin, ); sense of humor in guiding (e.g., Pabel & Pearce, ); or the impact of attractiveness and seniority on tour guides (e.g., Tsai, Wang, & Tseng, ).…”
Section: Introductionmentioning
confidence: 99%